Profile of Educational Technology Use by Medical Students and Evaluation of a New Mobile Application Designed for the Study of Human Physiology. - Oliveira, Erica Y.; Crosewski, Nathalia I.; Silva, André L. M.; Ribeiro, Cibele T. D.; de Oliveira, Camila M.; Fogaça, Rosalvo T. H.; Dias, Fernando A. L. (Journal of Medical Systems, 2019)
Nowadays, smartphones represent an invaluable tool to access educational material; however, the available information is not always accurate or evidence-based. Therefore, we aimed to evaluate the use of technology by medical students and assess the effect of a newly developed mobile app for the study of human physiology. We used a standardised questionnaire to assess the profile of educational technology use, from which a mobile app (PhysioQuiz) was developed. The effectiveness and user opinion were assessed in a randomised controlled study (n = 110). Of 1022 students enrolled in medical school, 489 (47.9%) participated in the study. Of the respondents, 96.7% used mobile applications, with the main purpose being entertainment (94.7%) and study (81.9%). Only 6.1% reported use of physiology apps. PhysioQuiz use did not yield higher average grades (p = 0.48); however, user opinion demonstrated that it was useful for assisted learning (82.1%) and identification of non-learned content (78.6%) and considered a tool for self-assessment (89.3%). Mobile app use is widespread among medical students but there is a lack of human physiology education apps. A newly developed app for the study of human physiology was useful for assisted learning and considered a tool for self-assessment.